RANCANGAN MODEL PROSES MANUFAKTUR MESIN 3DPRINTING PORTABLE MODEL CARTESIAN - Frizki Yudiansyah (2020)
In the development of a product it is very necessary to satisfy the desires of consumers, the process requires the translation of technical drawings into a physical product or commonly called Prototyping. 3d printing machine is one of the printing machine to full fill the needs of prototyping by using Layered Manufacturing production process. Today, we are forced to be able to carry out activities easily and quickly, therefore we need goods with portable form so that they can be used easily. This research is expected to get the results of the manufacturing process of the 3d Printing machine that can be used easily and has low manufacturing costs. In the manufacturing process there are two noteworthy aspects in manufacturing process, the cost incurred and the quality of product. The final result of this research is to get a machine with a low manufacturing price and easy to use. It is recommended that the machine development process uses a larger bed size so that it can print workpieces with larger dimensions.